PELATIHAN DIGITALISASI MATERI PEMBELAJARAN BAHASA INGGRIS BERBASIS KEARIFAN LOKAL UNTUK PEMBELAJAR MUDA - Ratri, Devinta Puspita; Rahmawati, Femi Eka; Tyas, Peptia Asrining; Safitri, Mega (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
According to seminal hypotheses in Second Language Acquisition (SLA), human learns language better in the early age. The learning was also tremendiously advanced when it is comnbined with technology and use familiar topic with the learners’ surrounding. The aforementioned are beneficial to ultimate English language learning pertinent to young learners. Given that rationale, the present community service aims to conduct a workshop for Junior High School teachers in Malang. The workshop was intended to give training to teachers on how to developed instructional materials amalgamated with techonology. The event was purposefully equipted teachers with technology savvy to design instructional materials development. The workshop activities comprise training presentation from experts, implementation consisting of designing and presenting materials and obtaining feedback, and evaluation. The evalution consisted completing reflective questionnaire and class observation. Based on the evaluation, teachers obtained ideas to digitalize their instructional materials, and based on the observation students were well engaged to the classroom activities. For those reasons, digitalizing instructional materials is beneficial for teaching young learners.